2008
DOI: 10.1677/jme-08-0160
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of adrenal gland growth: signal integration by extracellular signal regulated kinases1/2

Abstract: The adrenal gland influences a multitude of processes during stress response, but also potently affects the immune system, glucose metabolism, electrolyte or water homeostasis, and cardiovascular functions. According to the present understanding, the adrenal cortex is tightly controlled by the hypothalamic-pituitary-adrenal axis. This axis involves hypothalamic CRH and pituitary ACTH which determine processes of adrenocortical growth and function. However, control of the adrenal gland comprises a plethora of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 154 publications
2
17
0
1
Order By: Relevance
“…We previously reported that POMC and NH 2 -terminal POMC fragment are elevated in the LTH fetus. Thus it appears that in addition to PKA, ERK1/2 may play a potential, albeit unresolved, role in ACTH-induced steroidogenesis (19). To our knowledge, these are the first studies elucidating a role for pERK1/2 on cortisol production in the late-gestation sheep fetal adrenal cortex under both normoxic and long-term hypoxic conditions.…”
Section: Discussionmentioning
confidence: 90%
“…We previously reported that POMC and NH 2 -terminal POMC fragment are elevated in the LTH fetus. Thus it appears that in addition to PKA, ERK1/2 may play a potential, albeit unresolved, role in ACTH-induced steroidogenesis (19). To our knowledge, these are the first studies elucidating a role for pERK1/2 on cortisol production in the late-gestation sheep fetal adrenal cortex under both normoxic and long-term hypoxic conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Calculations of explosions, light curves, and spectra are performed using the HYDro RAdiation transport (HYDRA) code (Hoeflich 1990;Hoflich 1995;Hoeflich 2003Hoeflich , 2009a. HYDRA solves the hydrodynamics using the explicit Piecewise Parabolic Method (PPM; Colella & Woodward 1984), detailed nuclear and atomic networks (Cyburt et al 2010;Kurucz 1994;Hoflich 1995;Seaton 2005), radiation transport including γ rays and positrons by variable Eddington Tensor solvers and Monte Carlo Methods (Mihalas & Mihalas 1984;Stone et al 1992;Hoeflich 2003;Hoeflich et al 1993;Hoeflich 2009b;Penney 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Ang 1-7 has vasodilatory and antiproliferative properties and antagonises the actions of Ang II (Roks et al 1999, Lambert et al 2008. It is well known that Ang II stimulates the growth of the zona glomerulosa (ZG) of the adrenal and aldosterone secretion; however, the role of Ang II in the zona fasciculata-reticularis (ZF-ZR) of the adrenal is less well established (Hoeflich & Bielohuby 2009, Hattangady et al 2012. It has been shown that Ang II stimulates growth, glucocorticoid secretion and steroidogenic capacity in cultured adrenal fasciculata-reticularis cells and adrenal growth in genetically hypertensive Lyon rats (Nussdorfer et al 1981, Finn et al 1988, Viard et al 1990, Clyne et al 1993, Lebrethon et al 1994, McEwan et al 1999, Aguilar et al 2004, Romero et al 2006.…”
Section: Introductionmentioning
confidence: 99%